Stability of stevioside in Stevia extraction - Nor Aini, Ahmad (2010)
Stevia leaves have sweet taste more than 300-400 times sweeter than sugar. There are many researches have been done to show the benefits of stevia to our health. Producers use many types of preservation techniques to increase the stevia shelf life. One of methods is by addition of food additives. Thus, the aims of this research is to determine the stability of the sweet components in stevia, stevioside and also effect of additives to the stevioside. In this research we use fresh and dried stevia leaves. The leaves are cut into small pieces and will be extracted in 1L of water at 100oC for 5 minutes. The stevia extractions are filtered to remove the leaves. Then the stevia extractions are divided into two categories, sample with additive and without additives. About 3g of solid citric acid is added into samples with additive. The sweetness and the acidity of the samples are analyzed for 21 days. Based on the data we found that the stevioside more stable in stevia extraction samples without additives. Addition of additives caused increased in the acidity of the samples and the stevioside undergo the hydrolytic breakdown into steviol glycosides. Thus the sweetness was decreased in 21 days. Fresh stevia extraction had capability to resist from microbial activities, since pH decreased as the protection from the microbial activities.